Improving Cognition with Nutraceuticals Targeting TGF-β1 Signaling - Margherita Grasso; Giuseppe Caruso; Justyna Godos; Angela Bonaccorso; Claudia Carbone; Sabrina Castellano; Walter Currenti; Giuseppe Grosso; Teresa Musumeci; Filippo Caraci (MDPI AG, 2021)
Rescue of cognitive function represents an unmet need in the treatment of neurodegenerative disorders such as Alzheimer's disease (AD). Nutraceuticals deliver a concentrated form of a presumed bioactive(s) agent(s) that can improve cognitive function alone or in combination with current approved drugs for the treatment of cognitive disorders. Nutraceuticals include different natural compounds such as flavonoids and their subclasses (flavan-3-ols, catechins, anthocyanins, and flavonols), omega-3, and carnosine that can improve synaptic plasticity and rescue cognitive deficits through multiple molecular mechanisms. A deficit of transforming growth factor-β1 (TGF-β1) pathway is an early event in the pathophysiology of cognitive impairment in different neuropsychiatric disorders, from depression to AD. In the present review, we provide evidence that different nutraceuticals, such as Hypericum perforatum (hypericin and hyperforin), flavonoids such as hesperidin, omega-3, and carnosine, can target TGF-β1 signaling and increase TGF-β1 production in the central nervous system as well as cognitive function. The bioavailability of these nutraceuticals, in particular carnosine, can be significantly improved with novel formulations (nanoparticulate systems, nanoliposomes) that increase the efficacy and stability of this peptide. Overall, these studies suggest that the synergism between nutraceuticals targeting the TGF-β1 pathway and current approved drugs might represent a novel pharmacological approach for reverting cognitive deficits in AD patients.